Obecność - doczesne oblicze wieczności - Glinkowski, Witold (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
Eternity is not only an impersonal factor of the world nor the conception that organizes our notion of time. More importantly eternity is presence – interpersonal connection and constancy of being towards one another. Understood in such way, it becomes not so much the eternity that refers to something, but the unfailing, unwaveringpresence of one man towards the other – such presence, that one can rely on. It is “asstrong as death”, but unlike death it raises hope. It is more than present time. Present refer to objects, which in a certain moment last “here and now”. Whereas eternity, as presence, is the expression of people's mutuality. It's icon can be “face” within the meaningof Levinas. It also brings to mind his category of infinity – prior to finitude anddetermining its understanding. Likewise the presence, it is a source concept, as it determinesexperiencing the phenomenon of being a person.